Circ_0004951 Promotes Pyroptosis of Renal Tubular Cells via the NLRP3 Inflammasome in Diabetic Kidney Disease - Wang, Yulin; Ding, Li; Wang, Ruiqiang; Guo, Yanhong; Yang, ZiJun; Yu, Lu; Wang, LiuWei; Liang, Yan; Tang, Lin (Frontiers in Medicine, 2022)
Background：Diabetic kidney disease (DKD) has become the leading cause of chronic kidney disease (CKD) in many countries. Recent studies have shown that circular RNA and pyroptosis play an important role in pathogenesis of DKD. Methods：We analyzed expression patterns of circRNAs in human kidney biopsy tissues obtained from type 2 DKD (n = 9) and nephrectomy (n = 9) patients. Next, we cultured human renal tubular epithelial cells (HK2) in high glucose condition and detected circ_0004951, miR-93-5p, NLR Pyrin Domain Containing 3 (NLRP3) inflammasome-related indicators and pyroptosis. Furthermore, we performed Bioinformatics analysis and dual-luciferase reporter assay to analyze the relationship among circ_0004951, miR-93-5p and NLRP3. Results： Circ_0004951 was significantly upregulated in kidney tissues from DKD patients and HK2 in high glucose condition vs control. Knockdown of circ_0004951 mediated a significant suppression of HK2 pyroptosis, while results from bioinformatics analysis revealed that circ_0004951 has binding sites with miR-93-5p and miR-93-5p could bind to NLRP3. Results from dual-luciferase reporter assay further corroborated this finding. Finally, observations from rescue experiments showed that down-regulation of miR-93-5p and upregulation of NLRP3 markedly attenuated the anti-pyroptosis and anti-inflammatory effects of circ_0004951 knockdown on HK2. Conclusion：Circ_0004951 promotes pyroptosis of renal tubular epithelial cells in DKD via the miR-93-5p/NLRP3 inflammasome pathway, suggesting its potential for clinical diagnosis and treatment of DKD.